Enforcing Energy Balance in Coherently Superimposed Optical Vortices - Jaime Cisternas; Jaime A. Anguita; Gustavo Funes (IEEE Photonics Journal)
The generation of optical beams with multiple, mutually coherent orbital-angular-momentum (OAM) modes using phase gratings is analyzed from the perspective of energy distribution and radial mode composition. We show that phase gratings designed with equally weighted Laguerre–Gauss (LG) modes will generate beams with uneven energy distribution among OAM components. This unwanted outcome cannot be corrected by adjusting the width of the illuminating beam. We propose a way to design phase gratings that will produce a uniform energy distribution among the constituent OAM states after illumination while minimizing the content of high radial modes. This method is based on a generalized definition for the LG modes that take advantage of the freedom to select their radial scales.